2016
DOI: 10.1002/anie.201603455
|View full text |Cite
|
Sign up to set email alerts
|

{[CuSn5Sb3]2−}2: A Dimer of Inhomogeneous Superatoms

Abstract: Reaction of the binary Zintl anion (Sn2 Sb2 )(2-) with the β-diketiminato complex [LCu(NCMe)] (L=nacnac=[(N(C6 H3 (i) Pr2 -2,6)C(Me))2 CH](-) ) in ethylenediamine or DMF affords the ternary cluster dimer {[CuSn5 Sb3 ](2-) }2 (1) as its [K(crypt-222)](+) salt. The chemical formulation of 1 is supported by energy-dispersive X-ray spectroscopy (EDX) and quantum chemical calculations. Each monomeric part of the dimer represents a trimetallic "[CuSn5 Sb3 ](2-) " cluster, with an architecture in between a tricapped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 86 publications
3
32
1
Order By: Relevance
“…Therefore, the obtained clusters are strongly affected by their thermodynamic stability. [28] In this study, we demonstrate control of the valence electrons in superatomic gallium clusters [26,27,29,30] using our superatom synthesizer, that is, fourth generation dendritic polyphenylazomethines (DPAs). [31] Gallium is known to have a low melting point compared to other metals in the bulk state.…”
Section: Doi: 101002/adma201907167mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the obtained clusters are strongly affected by their thermodynamic stability. [28] In this study, we demonstrate control of the valence electrons in superatomic gallium clusters [26,27,29,30] using our superatom synthesizer, that is, fourth generation dendritic polyphenylazomethines (DPAs). [31] Gallium is known to have a low melting point compared to other metals in the bulk state.…”
Section: Doi: 101002/adma201907167mentioning
confidence: 99%
“…Although these approaches are sophisticated and allow variations in the clusters possible by changing the type of protecting ligands or synthesis conditions, they are basically thermodynamic syntheses. Therefore, the obtained clusters are strongly affected by their thermodynamic stability 28…”
mentioning
confidence: 99%
“…We recently reported that [K(crypt‐222)] 2 (Sn 2 Sb 2 ) reacts with [LCu(NCMe)] (L=nacnac=[(N(C 6 H 3 i Pr 2 ‐2,6)C(Me)) 2 CH] − ) in either 1,2‐diaminoethane (en) or dimethylformamide (DMF) to afford the dimer [(CuSn 5 Sb 3 ) 2 ] 4− as the [K(crypt‐222)] + salt . In this anion, the Cu + ions are not in endohedral positions, but rather are incorporated into the shells of the cluster monomers.…”
Section: Figurementioning
confidence: 99%
“…We explore, which of the homoatomic motifs can be mimicked this way, in the sense of the pseudo element concept, or where there are limits owing to a misfit in atomic/ionic radii affording either no products or other structural motifs , . Furthermore, binary anions of the type ( E 14 2 E 15 2 ) 2– proved to be excellent precursors to larger multi‐metallic clusters . Recently, we extended this concept to the lighter P 4 analogue (Ge 2 P 2 ) 2– …”
mentioning
confidence: 99%
“…By extraction of solid mixtures of the nominal compositions K 2 E 14 E 15 or K 2 E 14 2 E 15 2 (cf. the successful use of both stoichiometries as precursor solids for binary anions of other elemental combinations), , in en/crypt‐222, we obtained novel anions comprising seven atoms.…”
mentioning
confidence: 99%